FRACTIONAL RADIOFREQUENCY FACIAL TREATMENT: AN INTEGRATIVE LITERATURE REVIEW - Neves, Priscila Mickelly Araújo; Araújo, Larissa Silva; Corrêa, Felipe Braga; Alves, Eliandrea Lima Castro; Goto , Lucicleide Kubiczewski; de Assunção, Ana Carolina Cantuária; de Oliveira , Yuri Vinícius; Pimentel, Renê Silva (Editora Impacto Científico, 2025)
Facial aging is a natural process characterized by structural changes in the skin, such as sagging, wrinkles, and loss of elasticity, directly impacting self-esteem and quality of life. In this context, fractional facial radiofrequency emerges as an effective non-invasive therapeutic alternative for skin rejuvenation. This study aimed to analyze the main benefits of fractional facial radiofrequency through an integrative literature review. The search was conducted in the PubMed, SciELO, and LILACS databases, considering publications between 2018 and 2024. Six articles that met the inclusion criteria were selected, demonstrating positive results regarding improved skin texture, firmness, reduction of wrinkles, scars, and blemishes, as well as stimulation of collagen production. The findings show that, in addition to physiological effects, the technique promotes emotional benefits, such as strengthening self-esteem, especially among adult and elderly women. Despite the promising results, the need for more standardized clinical studies with a larger number of participants and long-term follow-up is highlighted. Therefore, fractional radiofrequency is an effective, safe, and minimally invasive therapeutic technique for skin rejuvenation, promoting satisfactory aesthetic results with positive impacts on self-esteem and quality of life. DOI: https://doi.org/10.56238/edimpacto2025.091-028